Pengembangan Media Assemblr Studio Berbasis 5e Untuk Meningkatkan Hasil Belajar Siswa Kelas V Sekolah Dasar Negeri 111923 Bulusari T.A 2023/2024 - Tri Abdi Mardinawan; Imelda Free Unita Manurung (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to develop an interesting and fun learning media based on Assemblr Studio. Assemblr is one of the best 3D/4D applications that encourages students to learn and understand what they learn through building and designing. This research uses the Research & Development (R&D) research method which is in accordance with the research objectives, namely developing assemblr studio-based learning media. Research & Development (R&D) is a research method used to develop or validate products for education and learning. The results of this study are the feasibility of 5E-based assemblr studio learning media, seen from the results of validation by experts including material experts and media experts. The material expert conducted 2 stages where stage 1 obtained a percentage of 60% feasibility and stage 2 obtained a percentage of 80% with an average percentage of feasibility of 70%. Media experts conducted 1 stage and obtained a feasibility percentage of 77% including the very feasible category so that this learning media can be used in learning theme 8 subtheme 1 learning 1. So that the conclusion obtained from this research and development is that the 5E-based Assemblr Studio learning media to improve student learning outcomes is declared feasible to use in learning.